Influence of income difference on carbon and material footprints for critical metals: The case of Japanese households - Yosuke Shigetomi; Keisuke Nansai; Shigemi Kagawa; Susumu Tohno (Journal of Economic Structures, 2016)
This study simultaneously analyzed the carbon and material footprints for three critical metals (neodymium, cobalt, and platinum) in Japanese households with different income levels. These metals are critical for new energy technologies, such as electric vehicles and rechargeable batteries, and are thus central to carbon footprint reductions. The policy implications of the trade-offs between GHG mitigation and critical metal consumption are considered within the context of differences in income. A global link input-output model representing national and international supply chains was employed to quantify the footprints according to household income quintile.In addition, the square root scaling method was used to compare footprints among households, considering differences in household size and their footprint characteristics. It is found that the degree of similarity among the carbon and material footprints for the three target metals was not very high [Spearman's rank correlation coefficients between them were 0.34 (neodymium), 0.63 (cobalt), and 0.10 (platinum)], implying that differences in relative household demand should be carefully considered based on differences in target footprints. The results of this study were compared to a similar study conducted in the UK to identify similarities and differences among footprints. In both countries, the carbon footprint intensity of household expenditure decreases as household income increases. The findings of this study also revealed that, in contrast to the case of carbon footprints, the material footprint intensities of household expenditure rise as household income increases, particularly in the case of neodymium. Consequently, the implementation of subsidies aimed at reducing carbon footprints and stimulating the economy should carefully consider the concomitant increase in material footprints. Importantly, such considerations are not only applicable to developed countries, but also emerging countries, the living standards of which are expected to increase markedly in the near future.
Keywords: 330